PJMHS 2021
DOI: 10.53350/pjmhs211582350
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Diagnosis by Genetic Markers Protein P-53, p16, C-MYC, N-MYC, Protein K-Ras, and Gene Her-2 Neu is this possible? Tumor Diagnosis by Genetic Markers C-MYC, N-MYC, Protein P-53, p16

Abstract: Currently, cancer is among the leading causes of death in the world. It is the correct diagnosis that gives the patient a better chance of healing. The detection of genetic markers, macromolecules that are produced directly by the tumor or by the host, has the potential to be one of the diagnostic tests. This paper is a review article, with the objective of addressing tumor markers c-MYC, n-MYC, protein p-53, protein Kras, and the gene HER-2 neu regarding the diagnosis and prognosis of patients with cancer, st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(6 citation statements)
references
References 37 publications
1
5
0
Order By: Relevance
“…However, Kebede et al reported that half of NSIs occurred in women [25]. There was a significant relationship between the gender and needle stick injuries (p = <0.001) that was in line with the study of Pili et al [26], [27].…”
Section: Prevalence Of Nsis Among Hcwssupporting
confidence: 75%
“…However, Kebede et al reported that half of NSIs occurred in women [25]. There was a significant relationship between the gender and needle stick injuries (p = <0.001) that was in line with the study of Pili et al [26], [27].…”
Section: Prevalence Of Nsis Among Hcwssupporting
confidence: 75%
“…The Current work is a preliminary trial for the selection of pharmacological molecules with inhibitory potential of the normal and mutated androgen receptor (T877A). 11 19 …”
Section: Methodsmentioning
confidence: 99%
“…During the COVID-19 pandemic, neuromuscular complications were evident [ 25 ]. Between 30% and 50% of the ICU patients presented generalized neuromuscular weakness during their hospitalization that appears to be secondary to CIM and CIP or their combination, causing prolongation and increasing admission time and ventilation duration in the ICU [ 25 , 26 ].…”
Section: Literature Reviewmentioning
confidence: 99%